La técnica y el método de Abel Carlevaro: una propuesta de revisión y ordenamiento del Cuaderno nº4 de la Serie Didáctica para Guitarra - Huayma Yepun Tulian Labiano (2020)
Abel Carlevaro is considered a reference in the classical guitar world; his activity as a pedagogue, performer and composer has influenced many generations of guitarists. His theoretical and practical writings, which deal with instrumental technique, represent a fundamental contribution to contemporary guitar. This production contains four exercise books - Serie Didáctica (CARLEVARO, 1972-1973) and the theoretical book Escuela de la guitarra - Exposición de la teoría instrumental (CARLEVARO, 1978). After the deep study of these works it is possible to observe that some aspects are not completely solved. From this observation, the question that guides this work arises: How could the technical approach carried out by Carlevaro be revised and improved? In order to face this question, we propose, in the first place, to investigate the concept "technique" from different perspectives and to review the history of guitar methods; to recognize the continuities and ruptures that are present in Carlevaro's technical-didactic approach. In second place, it is proposed to study Carlevaro's method punctually. Here, four types of questions/problems present in the Serie Didáctica are identified (lack of classification of the exercises according to their typology / lack of organization of the exercises according to the level of difficulty / inconsistency in the written explanations / no works where to apply the exercises) and defined criteria are proposed to objectively approach each one. Finally, an analysis and reordering of Cuaderno No. 4 of the Serie Didáctica is carried out, according to the criteria defined above. The treatment of the four types of questions/problems in this book allowed: to classify typologically 115 exercises and to select only 69 as basic (essential); to organize in three levels of difficulty those considered basic exercises; to identify the points that must be clarified in the written explanations; and finally, to apply the basic exercises to compositions in the form of simple studies.